The Brassica napus receptor‐like protein RLM2 is encoded by a second allele of the LepR3/Rlm2 blackleg resistance locus. Issue 7 (3rd February 2015) - Larkan, Nicholas J.; Ma, Lisong; Borhan, Mohammad Hossein
Summary Leucine‐rich repeat receptor‐like proteins (LRR‐RLPs) are highly adaptable parts of the signalling apparatus for extracellular detection of plant pathogens. Resistance to blackleg disease of Brassica spp. caused by Leptosphaeria maculans is largely governed by host race‐specific R‐genes, including the LRR‐RLP gene LepR3. The blackleg resistance gene Rlm2 was previously mapped to the same genetic interval as LepR3. In this study, the LepR3 locus of the Rlm2Brassica napus line 'Glacier DH24287' was cloned, and B. napus transformants were analysed for recovery of the Rlm2 phenotype. Multiple B. napus, B. rapa and B. juncea lines were assessed for sequence variation at the locus. Rlm2 was found to be an allelic variant of the LepR3 LRR‐RLP locus, conveying race‐specific resistance to L. maculans isolates harbouring AvrLm2. Several defence‐related LRR‐RLPs have previously been shown to associate with the RLK SOBIR1 to facilitate defence signalling. Bimolecular fluorescence complementation (BiFC) and co‐immunoprecipitation of RLM2‐SOBIR1 studies revealed that RLM2 interacts with SOBIR1 of Arabidopsis thaliana when co‐expressed in Nicotiana benthamiana. The interaction of RLM2 with AtSOBIR1 is suggestive of a conserved defence signalling pathway between B. napus and its close relative A. thaliana.